Identification of oncogenes and tumor-suppressor genes with hepatocellular carcinoma: A comprehensive analysis based on TCGA and GEO datasets - Zhu, Yue; Wang, Yanfei; Hu, Mengyao; Lu, Xiaoting; Sun, Guoping (Frontiers in Genetics, 2023)
Aim: Existing targeted therapies for hepatocellular carcinoma (HCC) are resistant and have limitations. It is crucial to find new HCC-related target genes. Methods: RNA-sequencing data of HCC were gathered from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets. Initially, differentially expressed genes (DEGs) between normal and tumor tissues were identified from four GEO datasets, GSE36376, GSE102079, GSE54236, and GSE45267. GO terms and KEGG pathway enrichment analyses were performed to explore the potential biological functions of DEGs. PPI network under the construction by using the STRING database, up-regulated and down-regulated hub genes were defined through 12 topological approaches. Subsequently, analyze the correlation bounded by up-regulated genes and down-regulated genes in diagnosis, prognosis, and clinicopathological features of HCC. Beyond a shadow of a doubt, the key oncogene PBK and tumor suppressor gene F9 were screened out, and the specific mechanism was investigated through GSEA enrichment analysis and immune correlation analysis. The role of PBK in HCC was further verified by Western Blot, CCK8, transwell and tube formation experiments. Results: CDCA5, CDC20, PBK, PRC1, TOP2A, and NCAPG are good indicators of HCC diagnosis and prognosis. Low expression of F9, AFM, and C8B indicates malignant progression and poor prognosis of HCC. PBK was found to be closely related to VEGF, VEGFR, PDGFR pathways. Experiments show that PBK promotes HCC cell proliferation, migration, invasion, and promotes tube formation in HUVEC cells. F9 was negatively correlated with the degree of immune infiltration, and low expression of F9 suggested a poor response to immunotherapy. Conclusion: The role of HCC-related oncogenes and tumor suppressor genes in diagnosis and prognosis was identified. In addition, we have found that PBK may promote tumor proliferation through angiogenesis, and F9 may be a predictor of tumor immunotherapy response.